Intelligent control system for the electric vehicle heat pump air conditioner based on machine learning - Miao, Zehua (Frontiers in Energy Research, 2023)
As one of the most energy-consuming auxiliary subsystems of electric vehicles, it is imperative to adopt heat pump air conditioning to replace the original PTC heating system when the existing battery technology cannot make a breakthrough improvement. Many researchers have tried to apply machine learning models to the study of heat pump air conditioning control systems for electric vehicles. In this paper, firstly, the advantages and disadvantages of different heat pump models for new energy vehicles are analyzed and compared. Secondly, it analyzes some of the difficulties to be faced in the design of heat pumps for new energy vehicles and evaluates various existing solutions by combining the studies of scholars from various countries. Finally, suggestions are made for the future development direction of heat pump systems. The purpose of this paper is to systematically analyze the latest research results on heat pump air conditioning control systems for electric vehicles and to lay the foundation for further optimization of heat pump air conditioning design for electric vehicles.